A new pump selection method for large-power PV irrigation systems at a variable frequency. (15th October 2018) - Almeida, R.H.; Ledesma, J.R.; Carrêlo, I.B.; Narvarte, L.; Ferrara, G.; Antipodi, L.
Highlights: A new pump selection method for PV irrigation systems is proposed. A comparison between the pump selected with the new and traditional methods is done. The water volume increases 7.2–21.0% when compared to the traditional method. The pump efficiency increases 4.3–5.3% when compared to the traditional method. The proposed model has already been implemented in SISIFO. Abstract: This paper presents a new method for selecting a pump for large-power PV irrigation systems working at a variable frequency. This can have a significant impact since the traditional way of selecting the pump is based on maximizing the efficiency of pump in the duty point at a certain single operating frequency, which is not useful for PV irrigation systems working at a variable frequency. The proposed method starts by considering the pumps with H-Q curves with a high slope and the duty point in the right-hand third of the curve to assure a wide range of operating frequencies. Then, the efficiency within the whole range of frequencies is evaluated. An example of a performance comparison between the pumps selected with the new and traditional methods has been carried out. Results show that by using the new method, the yearly volume of water pumped increases by 7.2–21.0% and the pump efficiency by 4.3–5.3%. Finally, it is important to mention that the proposed method has already been implemented in the SISIFO tool, able to simulate PV irrigation systems.